1998
DOI: 10.1046/j.1365-2427.1998.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating age and growth in long‐lived temperate freshwater crayfish using lipofuscin

Abstract: 1. In ecological studies on freshwater crayfish, determination of basic population parameters is often complicated by the lack of a suitable age estimation method. 2. Previously, lipofuscin age pigment in the olfactory lobe cell masses (OLCM) of short‐lived tropical crayfish has been used for accurate age determination. Here we present the first test of this method on a longer‐lived, temperate species, the signal crayfish, Pacifastacus leniusculus. 3. Confocal fluorescence microscopy and image analysis of hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 14 publications
2
45
0
1
Order By: Relevance
“…By using external tags or similar markings in molting periods of less frequency, it is possible to avoid the use of invasive techniques for 'structuring' (i.e. ageing) crayfish populations, such as the analysis of lipofuscin granules (Belchier et al, 1998), and the recapture method of Abrahamsson (1965) and its modifications (Burič et al, 2008;Scalici et al, 2010a), the latter representing the beginning of possible infections that can compromise the health of marked individuals. Invasive methods concern heat-marking on the coxae or carapace by soldering guns and the use of (1) passive integrated transponder tags (Wiles and Guan, 1993;Bubb et al, 2002), or (2) visible elastomer tags (Partanen and Penttinen, 1995;Jerry et al, 2001).…”
Section: Table I Results Of the Series Of Pairwise Kruskall-wallis Tementioning
confidence: 99%
“…By using external tags or similar markings in molting periods of less frequency, it is possible to avoid the use of invasive techniques for 'structuring' (i.e. ageing) crayfish populations, such as the analysis of lipofuscin granules (Belchier et al, 1998), and the recapture method of Abrahamsson (1965) and its modifications (Burič et al, 2008;Scalici et al, 2010a), the latter representing the beginning of possible infections that can compromise the health of marked individuals. Invasive methods concern heat-marking on the coxae or carapace by soldering guns and the use of (1) passive integrated transponder tags (Wiles and Guan, 1993;Bubb et al, 2002), or (2) visible elastomer tags (Partanen and Penttinen, 1995;Jerry et al, 2001).…”
Section: Table I Results Of the Series Of Pairwise Kruskall-wallis Tementioning
confidence: 99%
“…Despite the heterogeneous composition and genesis of lipofuscin, its relationship with aging has been demonstrated in many groups of crustaceans such as krill (NICOL et al, 1991), amphipods (BLUHM et al, 2001), clawed (O'DONOVAN & TULLY, 1996SHEEHY et al, 1996;WAHLE et al, 1996;SHEEHY et al, 1999;CASTRO et al, 2002;) and spiny lobsters (SHEEHY et al, 1998), crayfish (SHEEHY, 1990a;SHEEHY et al, 1994;BELCHIER et al, 1998) and shrimps, both caught in the wild or raised in aquaculture (SHEEHY et al, 1995;VILA et al, 2000;MEDINA et al, 2000;SOBRINO et al, 2001;PEIXOTO et al, 2002;VILA GORDILLO, 2005). These studies, based also on animals kept in controlled conditions, allowed the improvement of extraction and methods of analysis, as well as the confirmation that, regardless the sex, lipo- Medit.…”
Section: Discussionmentioning
confidence: 99%
“…Those specimens without obvious pigment granules do not necessarily lack the pigment, but granules may not have been detectable with the applied methodology. Although we tried to include specimens close to the known maximum size of the species, age-pigment concentrations ranged an order of magnitude lower than measured in species from lower latitudes Belchier et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The author concluded that the histologically based quantitative method with concurrent visual microscopic veri®cation of in situ morphological lipofuscin's¯uorescence and histochemical attributes is the only reliable method for quanti®cation. Several recent studies have been attempted to assess the applicability of morphological lipofuscin as an age marker (O'Donovan and Tully 1996; Belchier et al 1998;Sheehy et al 1998). Besides E. superba (Sheehy 1990a), no other species from high latitudes has been studied until now.…”
Section: Introductionmentioning
confidence: 99%